A novel method for improving the performance of thermoacoustic electric generator without resonator. (15th February 2016) - Wang, Yufang; Li, Zhengyu; Li, Qing
Highlights: A thermoacoustic electric generator without resonator is studied. A novel impedance modulation method of filling phase modulation object is proposed. Maximum output electric power of 73.31 W with 14.06% system efficiency is obtained. Maximum system efficiency of 14.12% with 71.25 W output electric power is achieved. Abstract: A thermoacoustic electric generator without resonator designed for aerospace application is discussed in this study, which is developed by a traveling-wave looped-tube thermoacoustic heat engine coupling with two linear alternators directly. A novel method of filling phase modulation object in the acoustic power output port is proposed to improve the performance of the thermoacoustic electric generator. The experimental results show that the ellipsoid makes the most significant influence among sphere, cylinder and ellipsoid serving as phase modulation object. Varying the major axis of the ellipsoid only, the influence of it increases first and then decreases. The ellipsoid fixed in different positions makes different effects. The maximum output electric power of 73.31 W and the maximum system efficiency of 14.12% are obtained in the upper and middle positions respectively.